EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KELAPA SAWIT (Elaeis quenensis Jacq) DI DESA TOLOLE KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - W, Wahyudin.; Monde, Anthon; Rahman, Abdul (AGROTEKBIS, 2016)
This study aims to determine the suitability of land planted oil palm (Elaeis quenensis Jacq). In the region of the Tolole Village of the District Ampibabo, Parigi Moutong District. The method used in this research is the method survei. Penelitian is implemented by way of soil sampling in the field, followed by laboratory analysis. Research activities include four (4) phases : preparation, field activities, laboratory analysis and data processing, map making and the preparation of reports. The results showed that the class suitability of land for oil palm trees (Elaeis quenensis Jacq) in the study area are Class S2 (appropriately enough) in the SPL I, II , III , and IV with total area of 1573.82 ha. Key Words: Land suitability, land survey.